The association of racial attitudes and spiritual beliefs in post-apartheid South Africa - Smith, Timothy B. (Mental health, religion & culture, 2007)
Previous research has investigated the complex association between religious beliefs and racism. Many studies have found that fundamentalist religious beliefs are positively associated with racial prejudice among European and European American populations. However, few studies have examined whether this association is found in other cultures or whether the association also characterizes spiritual beliefs. Data from 493 South African university students from three racial backgrounds revealed significant differences among the groups. A positive association between fundamentalism and racial prejudice was found among participants, but general spiritual beliefs were negatively associated with racist attitudes. The results emphasize the need to address contextual factors that influence the association between religious beliefs and racism within a given culture.